1977
DOI: 10.1084/jem.145.4.907
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the antigenic complex recognized by T lymphocytes II. T-cell activation by direct modification of macrophage histocompatibility antigens.

Abstract: In order to analyze the molecular structures involved in T-cell recognition we developed an in vitro primary response against alloantisera bound to histocompatibility antigens in which nonimmune guinea pig T cells can be sensitized and subsequently challenged in tissue culture with antisera-treated macrophages. If macrophages were incubated with alloantisera directed against the I-region-associated (Ia) antigens of the guinea pig major histocompatibility complex (MHC) T cells could be sensitized to the antiser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The work of Shevach and co-workers (6,7,51,52), Erb and Feldmann (46), Pierce et al (41), and ourselves (10,11), has established that T-cell interaction with antigen bound to the MoP surface is under the control of MHC-linked genes expressed in the MoP. In at least one of these studies (41) all of the control was shown to be at the level of helper T-cell/Mdp interactions, with the MHC type of the responding B cell irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Shevach and co-workers (6,7,51,52), Erb and Feldmann (46), Pierce et al (41), and ourselves (10,11), has established that T-cell interaction with antigen bound to the MoP surface is under the control of MHC-linked genes expressed in the MoP. In at least one of these studies (41) all of the control was shown to be at the level of helper T-cell/Mdp interactions, with the MHC type of the responding B cell irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has previously been shown that alloantisera directed against strain 2 or strain 13 macrophage Ta antigens inhibited the in vitro proliferation of T cells in an MLR (Greineder et al 1976) we attempted to use anti-la sera in a third attempt to eliminate the MLR in the in vitro T cell priming with anti gen-pulsed allogeneic macrophages. However, by this technique we made the fortuitous observation that anti-la bound to macrophages created a new antigeneic determinant recognized by T cells (Thomas & Shevach 1977a). When strain 13 T cells were incubated with syngeneic macrophages in the presence of anti-Ia.1,377 serum in the first culture and transferred to fresh strain 13 macrophages in the presence of anti-Ia.1,3,7 serum in the second culture, substantial T cell activation occurred (Table I, line 4).…”
Section: T Cell Sensitization To Alloantibody-modified Macrophagementioning
confidence: 99%
“…Antigenic structures on their surface (la antigens) form an important part of the antigenic complex recognized by lym phocytes (23). The highest in vitro stimulation of lymphocytes achieved by hapten-modified macrophages could be explained by the fact that by this method the optimal antigenic complex is formed.…”
Section: Discussionmentioning
confidence: 99%